An integrated framework for sustainable retrofitting of existing university buildings - Eman Khalaf Allah Ahmed; Khaled M. Dewidar; Youssef Abd El-Hakeem; Marianne Nabil Guirguis (Discover Sustainability)
Abstract Energy consumption is a global problem facing the world. According to the latest studies, and there is a great opportunity of reduction of the carbon dioxide emissions by re-considering the existing non-residential buildings, such as educational, commercial, and administrative facilities. This study investigates the concepts of sustainable retrofitting of existing university buildings. A framework for sustainable retrofitting of university buildings is developed. The framework illustrates the workflow including the different phases of retrofitting, and the possible choices for optimizing energy consumption within the different systems of university buildings. Thus, reaching a step towards green buildings by working on the existing built environment, not only new construction projects.